Ethnomedicine in Magar Community of Dhadhing District, Central Nepal - Poudel, Sabita; Gautam, Chinta Mani (Journal of Plant Resources, 2008)
A study was made to document the knowledge on medicinal plants of Magar community, living in the Gauthale Village, Dhadhing district in the hilly region of Nepal. The village had 117 households, and total population was 870 persons during a fieldwork. The information was collected in direct interaction with the inhabitants through Participatory Rural Appraisal technique. This study recorded 62 species, which belong to 41 families, in use for preparing 72 medicinal remedies. Trees were the primary sources of medicinal material in terms of the total percentage of species followed by herbs. Of the plant parts, root was used most frequently for preparing medicinal remedies followed by the bark and leaf. Gastro-intestinal and respiratory tract infections were found as common health problems for treatment of which 28% and 25% of known remedies are used, respectively. The result of this study revealed that the knowledge of medicinal plants in the Magar community is limited only to aged persons and healers. The dependence on plants for medicine is associated with their traditional belief of effectiveness of plant remedies and poverty. Due to excessive harvesting practices, Clerodendrum viscosum and Ardisia sp have disappeared and Callicarpa macrophylla, Swertia nervosa, Sida cordata, and Micromeria biflora are becoming rare from the area. So, this study suggests that integrated efforts, both at governmental and non-governmental levels should be made for sustainable use of resources raising the awareness of local people on medicinal plants that finally helps to conserve the rare and disappearing species from the area. Sustainable use of resources requires involvement of experienced and knowledgeable persons of the community. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 80-86